Alginate microparticles as novel carrier for oral insulin delivery - Reis, Catarina Pinto (2007)
Alginate microparticles produced by emulsification/internal gelation were investigated as a promising carrier for insulin delivery. The procedure involves the dispersion of alginate solution containing insulin protein, into a water immiscible phase. Gelation is triggered in situ by instantaneous release of ionic calcium from carbonate complex via gentle pH adjustment. Particle size is controlled through the emulsification parameters, yielding insulin-loaded microparticles. Particle recovery was compared using several washing protocols. Recovery strategies are proposed and the influence on particle mean size, morphology, recovery yield (RY), encapsulation efficiency, insulin release profile, and structural integrity of released insulin were evaluated. Spherical micron-sized particles loaded with insulin were produced. The recovery process was optimized, improving yield, and ensuring removal of residual oil from the particle surface. The optimum recovery strategy consisted in successive washing with a mixture of acetone/hexane/isopropanol coupled with centrifugation. This strategy led to small spherical particles with an encapsulation efficiency of 80% and a RY around 70%. In vitro release studies showed that alginate itself was not able to suppress insulin release in acidic media; however, this strategy preserves the secondary structure of insulin. Particles had a mean size lower than the critical diameter necessary to be orally absorbed through the intestinal mucosa followed by their passage to systemic circulation and thus can be considered as a promising technology for insulin delivery. Biotechnol. Bioeng. 2007;96:977-989. © 2006 Wiley Periodicals, Inc.